Analisis Faktor-Faktor Yang Mempengaruhi Opini Audit Going Concern Pada Perusahaan Manufaktur Tahun2011-2014 - Subandono, Subandono; , Drs. Wahyono, Ak, MA (2016)
Intention of this research is to know influence of bankruptcy prediction, growth of company, reputation of KAP, previous year audit opinion and company size measure to audit opinion of going concern. This research is [conducted at Manufacturing Business in Indonesia. This research use quantitative approach, because used data in form of numbers. Determination of sampel in this research use method of purposive sampling. The research test which is used in this analysis of logistics regression constructively on SPSS 21 . Result of research showing that variable of bankruptcy prediction and growth of company dont have an effect on significant to audit opinion of going concern, while reputation variable of KAP, previous year audit opinion and company size measure have an effect on significant to audit opinion of going concern.